Correlations do not show cause and effect: Not even for changes in muscle size and strength - Dankel, S. J.; Buckner, S. L.; Jessee, M. B.; Mouser, J. G.; Mattocks, K. T.; Abe, T.; Loenneke, J. P. (Sports Medicine, 2018)
It is well known that resistance exercise results in increased muscle strength, but the cause of the improvement is not well understood. It is generally thought that initial increases in strength are caused by neurological factors, before being predominantly driven by increases in muscle size. Despite this hypothesis, there is currently no direct evidence that training-induced increases in muscle size contribute to training-induced increases in muscle strength. The evidence used to support this hypothesis is exclusively correlational analyses and these are often an afterthought using data collected to answer a different question of interest. Not only do these studies not infer causality, but they have inherent limitations associated with measurement error and limited inter-individual variability. To answer the question as to whether training-induced increases in muscle size lead to training-induced increases in strength requires a study designed to produce differential effects on muscle size based on group membership (i.e., one group increases muscle size and one does not) and observe how this impacts muscle strength. We have performed studies in our laboratory in which muscle strength increases similarly independent of whether muscle growth is or is not present, illustrating that the increases in muscle strength are not likely driven by increases in muscle size. The hypothesis that training-induced increases in muscle size contribute to training-induced increases in muscle strength requires more appropriately designed studies, and until such studies are completed, this statement should not be made as there are no data to support this hypothesis.